2009
DOI: 10.1177/030089160909500315
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Markers for Ovarian Cancer at Chromosomes 1, 8 and 17 Revealed by Array CGH Analysis

Abstract: Our study has identified potential genomic markers of interest on chromosomes 1, 8 and 17 in ovarian cancer. Tumors showed a wide variety in the patterns of alteration, suggesting that alternative mechanisms of genomic instability may play a role in this tumor type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…In addition, TBX2 was amplified in pancreatic cancer cell lines [10]. It has been reported that TBX2 is a specific genomic marker for late-stage ovarian cancers [12]. Similarly, TBX2 has also been recognized as prognostic markers in bladder cancer [13].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, TBX2 was amplified in pancreatic cancer cell lines [10]. It has been reported that TBX2 is a specific genomic marker for late-stage ovarian cancers [12]. Similarly, TBX2 has also been recognized as prognostic markers in bladder cancer [13].…”
Section: Discussionmentioning
confidence: 96%
“…LIM and SH3 protein 1 mRNA is expressed ubiquitously at low basal levels in all normal human tissues, but is overexpressed in metastatic human breast cancer (Grunewald and Butt, 2008) and ovarian cancer (Grunewald et al, 2007b;Dimova et al, 2009). In a recent case -control study, LASP-1-expression correlated significantly with tumour size and nodal-positivity (Grunewald et al, 2007a).…”
mentioning
confidence: 98%
“…Both common and rare CNV regions may contribute to the development of cancer, and studies on CNV will be helpful for the treatment and chemoprevention of human ovarian cancer. To date, most investigations of CNV have been conducted using established cancer cell lines (Feuk et al, 2006;Grunewald et al, 2006;Dimova et al, 2009) because of difficulties in obtaining fresh human cancerous tissues. To allow in vivo studies, suitable animal models have been utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, LASP1, whose gene is located between 3,962,872 and 3,987,989 on chicken chromosome 27, is an actinbinding protein involved in peripheral cell extensions of epithelial cancer cells (Schreiber et al, 1998), and its inhibition disturbs the proliferation and migration of breast cancer cells (Grunewald et al, 2006). Based on array CGH analysis of human ovarian cancer, LASP1 is a strong candidate for an inducer of ovarian tumorigenesis (Dimova et al, 2009). …”
Section: Discussionmentioning
confidence: 99%